Taboo In Iraqi theater performance (Journal of the College of Basic Education, 2024)
The taboo represents an immensely targeted area in theater from text to display and research to address the forbidden in theatrical performance, which is on its way to join the name of a taboo- intellectual, social or ethnic taboo .And it is resulting in the disruption of the community‘s system, and so it is reflected in turn on the performer in Theatrical presentation as political, economic and social transformations and changes, produce extreme behavioral problems or partisan ideals such as da'is or militia. The research attempts to extrapolate multiple taboos and study their variants that have a negative or positive effect on theatrical performance, such as authoritarian taboos, political, sexual and others.